Characterization of ion-induced microstructural changes in oxygen irradiated Ti–6Al–4V. Issue 9 (3rd October 2022) - Dey, Santu; Dutta, Argha; Gayathri, N.; Mukherjee, P.; Roy, Tapatee Kundu
Abstract : The change in microstructure and mechanical properties ofTi–6Al–4V alloy due to 160 MeV O 6+ ion irradiation has been reported here. Detailed X-ray diffraction line profile analyses have been used to evaluate the microstructural parameters and characterize the nature of defects and their arrangements. The results indicate saturation of size of the coherent region, the dislocation density and its arrangement with dose, which points to an optimized final microstructure of irradiated material. This was also supported by the Vicker's microhardness measurements. Electron back scattered diffraction study was used to assess the changes in microstructure in terms of the evolution of misorientation boundaries within the grains due to irradiation-induced defects. All the results support the radiation resistance nature of Ti–6Al–4V alloy. Finally, comparison has been made with earlier proton irradiation results, and the difference has been related to the nature of the displacement cascade produced by light and heavy ions.